Morphological traits at distal end of femur. - Madhu, S; Suchismita, G; Neelam, V (Department of Surgery, UKM Medical Centre, 2013)
Bony changes in the form of facets and imprints due to squatting are more often seen at the lower end of femur than at the upper end. Because of a particular lifestyle and behaviour of various population groups, incidences of these traits differ. Such morphological traits should be understood as they could be a contributing risk factor for osteoarthritis and other rotational malalignment dysfunction of knee joint. Charles’ facet, tibial imprint and osteochondritic imprint are known to occur at the distal end of femur as a sequelae of squatting posture. This study was conducted to determine the prevalence of these facets and imprints on 152 adult femur of Indian origin in the Department of Anatomy, Maulana Azad Medical College, New Delhi, India. The significance of correlation between their occurrence with the side and gender of bone was determined using Chi-square test. The analysis of data indicated that Charles’ facet and medial tibial imprint occurred more often on right side with 100% incidence. Lateral tibial imprint showed a significant result with 84.2% incidence on the right side and 68.4% on the left side. Osteochondritic imprint also had a predominant occurrence on the right side. Charles’ facet was equally present in both male and female femora, however, imprints had a higher predominance in male femora with no significant results notified for gender variation.